Preliminary Study on Mortality of Catfish (Clarias macrocephalus) Fry Transported in Plastic Bags - Ali, Ahayaudin; Tg. Kamalden, Tg. Mohamad Izham; Abas, Adnan (1989)
Catfish (Clarias macrocephalus) fry were transported in plastic bags using clean water and pure oxygen at a ratio of 1:3. The rise in temperature and total ammonia during transportation was related to transportation time and packing density. Though dissolved oxygen increased when pure oxygen began to dissolve in the water during transportation it did not pose a problem. Low mortalities were observed among the less densely packed fish but post-transporatation mortalities were fairly high. Mortalities, however, could be reduced with the addition of salt (Nact) to the water.